From pearl millet domestication to harvests of surplus grains: associated archaeological data - (:unkn) unknown (My University, 2017)
Archaeology allows us to better understand the consequences of pearl millet agriculture on the evolution of West African society from the end of the IIIrd millennium BC. At this time, this grass acquired its domestic morphology at the borders of Mali, Niger and Algeria. This cereal cultivation – the oldest so far documented in subsaharan Africa – allowed: - excess productions of grains,- the development of specialized crafts,- an accentuation of social hierarchies,- the transmission of pearl millet cultivars to India,- and, from the Ist millennium BC, the appearance of warrior aristocracies.
Keywords: African Research